Evaluation of axial length and association with morphology of cataract - Vats, Vatsala; Gupta, Manisha; Aggarwal, Shantanu (International Journal of Research in Medical Sciences, 2021)
Background: Cataractogenesis is associated with alteration in the nature of lens epithelium. How a change in morphology of cataract relates to axial length and IOL power is an interesting area to explore. The aim of the study was to evaluate the association between axial length and age-related cataracts, and intra ocular lens (IOL) power in eyes undergoing cataract surgery. Methods: A cross sectional study was conducted from 2019 to 2020 on 550 eyes with age related cataract for morphology of cataract and axial length of eye. Data was analyzed using statistical software One-way ANOVA and Post HOC test. Results: Out of a total 550 eyes, 122 (22.2%) were Nuclear, 79 (14.4%) were PSC, and 349 (63.5%) were of Mixed morphology. Mean age of patients with PSC was 56.41±14.55 years, 58.52±14.16 years with Nuclear, and 62.88±9.86 years in Mixed morphology. This difference was found to be statistically significant with p value of 0.001. In this study, the mean axial length in eyes with only Nuclear, only PSC, and Mixed morphology, was measured to be 23.19±1.29, 23.26±0.91, 23.24±1.47 respectively. This was found to be statistically insignificant with p=0.92. The mean power intraocular lens 20.96±3.03 D in Nuclear Cataract, 21.25±2.39 D in PSC, and 21.25±2.60 D in Mixed cataract, and was statistically insignificant with p value of 1. Conclusions: This study suggests no impact of morphology of cataract on axial length or IOL power.